Financial Cryptography and Data Security c - Borisov, Nikita; Diaz, Claudia; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2021)
This double volume constitutes the thoroughly refereed post-conference proceedings of the 25th International Conference on Financial Cryptography and Data Security, FC 2021, held online due to COVID-19, in March 2021. The 47 revised full papers and 4 short papers together with 3 as Systematization of Knowledge (SoK) papers were carefully selected and reviewed from 223 submissions. The accepted papers were organized according to their topics in 12 sessions: Smart Contracts, Anonymity and Privacy in Cryptocurrencies, Secure Multi-Party Computation, System and Application Security, Zero-Knowledge Proofs, Blockchain Protocols, Payment Channels, Mining, Scaling Blockchains, Authentication and Usability, Measurement, and Cryptography.
Smart Contracts -- Anonymity and Privacy in Cryptocurrencies -- Secure Multi-Party Computation -- System and Application Security -- Zero-Knowledge Proofs -- Blockchain Protocols -- Payment Channels -- Mining -- Scaling Blockchains -- Authentication and Usability -- Measurement -- Cryptography.
Keywords: Cryptography; Data encryption (Computer science).; Operating systems (Computers).; Application software; Computer systems; Data protection; Cryptology; Operating Systems; Computer and Information Systems Applications; Computer System Implementation; Data and Information Security